End-of-Life Care, Dying and Death in the Islamic Moral Tradition أخلاق العناية في الإسلام: الرعاية الصحية عند نهاية العمر والاحتضار والموت - Ghaly, Mohammed (Brill, 2022)
Modern biomedical technologies managed to revolutionise the End-of-Life Care (EoLC) in many aspects. The dying process can now be "engineered" by managing the accompanying physical symptoms or by "prolonging/hastening" death itself. Such interventions questioned and problematised long-established understandings of key moral concepts, such as good life, quality of life, pain, suffering, good death, appropriate death, dying well, etc. This volume examines how multifaceted EoLC moral questions can be addressed from interdisciplinary perspectives within the Islamic tradition. Contributors Amir Abbas Alizamani, Beate Anam, Hamed Arezaei, Asma Asadi, Pieter Coppens, Hans Daiber, Khalid Elzamzamy, Mohammed Ghaly, Hadil Lababidi, Shahaboddin Mahdavi, Aasim Padela, Rafaqat Rashid and Ayman Shabana.